(untitled) (Journal Of Educational and Psychological Researches, 2022)
The purpose of the current research is to identify the most important problems that primary school students suffer from inside and outside the classroom from the point of view of their teachers. A sample of (100) male and female teachers was chosen from the Rusafa second Directorate for the academic year (2018-2019). The research tool was prepared after reviewing literature related to the issue of problems and difficulties facing students or students in the school stage and even at university. The researcher reached several results that were discussed in the fourth chapter, with a set of conclusions based on the results of the research, and come up with several recommendations and suggestions.